Clinical implication of tumor mutational burden in patients with HER2-positive refractory metastatic breast cancer. (3rd August 2018) - Park, Song Ee; Park, Kyunghee; Lee, Eunjin; Kim, Ji-Yeon; Ahn, Jin Seok; Im, Young-Hyuck; Lee, Choonghoon; Jung, Hun; Cho, Soo Youn; Park, Woong-Yang; Cristescu, Razvan; Park, Yeon Hee
ABSTRACT: This study explored the clinical implications of tumor mutational burden (TMB) in a well-defined HER2-positive metastatic breast cancer (MBC) patient population who had been previously treated but had subsequent disease progression. Whole exome sequencing was performed on formalin-fixed paraffin-embedded tumor samples and matched normal tissue. Among the 46 patients, 13 (28.3%) were estrogen receptor-positive and nine (19.6%) were progesterone receptor-positive by immunohistochemistry analysis. Twenty patients (43.5%) had recurrent MBC compared with de novo MBC (n = 26, 56.5%). Sixteen patients (34.6%) demonstrated more than 100 somatic non-synonymous SNV mutations, which was predefined as a high TMB. The median follow-up duration was 57.5 months. The median overall survival (mOS) differed significantly between low and high TMB status (44.9 months vs. 85.8 months, respectively, p = 0.016). In a multivariate Cox regression analysis, TMB was the only independent prognostic factor for good metastatic overall survival after adjusting for age and recurrence (Hazard ratio [HR] = 0.32, 95% confidence interval [CI], 0.103–0.998, p = 0.049). These data suggest that high TMB may be a prognostic marker for predicting good overall survival for patients undergoing conventional HER2-directed treatments and chemotherapy. Further, future clinical trials harnessing TMB may benefit by identifying an appropriate population who may have a favorable response to immunotherapy after recurrence following HER2-directed treatments.